ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Safitri, Anggie Munthia; Rohaeti, Euis Eti; Afrilianto, M (IKIP Siliwangi, 2018)
The aim of this research is to know the difficulties of reasoning ability include: (1) ability to give explanation related to Triangle and Segiempat using model, fact, nature, and relationship, (2) student ability to estimate answer and solution process of question given, (3) ) the ability of students to use patterns and relationships to analyze problems in Triangle and Quadrilateral, (4) ability to draw conclusions from every problem that exist both orally and in writing. The method used in this study by using qualitative methods. Population taken in this research is a student of SMP Negeri 1 Ngamprah class VII. Based on the research result, the average score of students' mathematical reasoning ability on triangle and quadrilateral material is 47%. Students who are able to determine the area and circumference of the flat wake tested in the solution of mathematical reasoning is 35%. While the number of students who are able to calculate the pattern n as much as 20%. Based on the data, it is concluded that there are students 'reasoning difficulties and students' mathematical reasoning ability at SMPN 1 Ngamprah is still low.